Cranial anatomy of Jeholosaurus shangyuanensis (Dinosauria: Ornithischia) from the Early Cretaceous of China - Barrett, Paul M.; Han, Feng-Lu (Zootaxa, 2009)
A detailed description of the skull and mandible of the Chinese cerapodan ornithischian dinosaur Jeholosaurus shangyuanensis (Lower Cretaceous, Yixian Formation) is presented for the first time and this information is used to reassess its phylogenetic position. Jeholosaurus can be distinguished from all other cerapodans on the basis of one autapomorphy (a row of small foramina on the nasal) and a character combination that is unique among ornithischians. Previously undescribed specimens add considerably to our knowledge of Jeholosaurus, providing new insights into its anatomy and ontogeny. Revised character scores increase the resolution of phylogenetic hypotheses and provide additional support for placement of Jeholosaurus within Ornithopoda.